When Delusions Become Shared: A Study of Folie À Deux in the Context of Paranoid Schizophrenia and Cultural Values - Vindyanita Simanjuntak (Jurnal Locus Penelitian dan Pengabdian, 2026)
Paranoid schizophrenia is a chronic psychotic disorder characterized by delusions and hallucinations. In certain conditions, delusions can be transmitted to closely related individuals, known as folie à deux or shared psychotic disorder. This phenomenon becomes more complex when influenced by cultural and social structures. This research aims to analyze the phenomenon of induced delusion in paranoid schizophrenia and examine the role of cultural values in shaping and maintaining shared delusions. This study employed a qualitative descriptive case study approach through clinical interviews, psychiatric examinations, and evaluation of interpersonal dynamics and cultural context. The findings indicate that the primary patient experienced paranoid schizophrenia with persecutory delusions, while the secondary patient developed induced delusions due to strong emotional attachment and intense interaction. Cultural factors, including family loyalty, collectivism, and patriarchal structure, reinforced the internalization of shared beliefs. Interventions such as pharmacotherapy, psychotherapy, and patient separation were effective in reducing symptoms. Shared psychotic disorder is influenced not only by individual factors but also by social interaction and cultural context. A biopsychosocial and culturally sensitive approach is essential for accurate diagnosis and effective management.